The Red Book: A Role-Based Portfolio for Non-Literate Immigrant Language Learners - Nuwenhoud, Annemarie (LESLLA Symposium Proceedings, 2015)
The Red Book is a portfolio that shows the development of LESLLA-learners. It is also used as teaching material. And thirdly, it can serve as an exam portfolio. The content of the Red Book is based on the roles that the students have in everyday life. They make it themselves, by drawing, colouring, pasting pictures and writing words in their Red Book. This turned out to be empowering for LESLLA learners. This article describes the setup and use of the Red Book portfolio in the former adult literacy program of a school in Amsterdam, The Netherlands. The Red Book portfolio can be applied in other adult literacy projects and classroom contexts as well. Some suggestions for the use of the Red Book portfolio in other contexts are being made, as well as a few recommendations for research.